Valuation of Cocoa Agroforestry Ecosystem Services: Impacts on Biodiversity and Farmer Income - Sinambela, Jose (Cattleya Darmaya Fortuna, 2025)
Cocoa agroforestry provides important ecosystem services such as biodiversity conservation, carbon storage, and support for pollination and nutrient cycling, which are often not market-valued. This study evaluates the economic value of non-market ecosystem services from local cocoa-agroforestry systems and their correlation with biodiversity and farmer income. Through a cocoa farmer survey and a contingent valuation approach, estimates of farmers' willingness to pay for the integration of shade trees in cocoa fields were obtained as a proxy for the value of ecosystem services. Results indicate that farmers value environmental services (e.g., pollinator habitat, soil fertility) at approximately IDR 2.5 million/ha/year. At the landscape level, cocoa agroforestry supports higher species richness than monoculture, with a loss of 60% of forest species if shade trees are removed. Trade-offs appear moderate: low-shade intensification increases short-term production by 40% but decreases carbon stocks and forest species. This study confirms that cocoa agroforestry can maintain biodiversity nearly equivalent to young secondary forests, while diversifying farmer incomes (fruit/timber). The economic valuation of ecosystem services justifies incentives (e.g., payment for ecosystem services) for farmers to maintain tree shade for the benefit of all.